Avian polyomavirus: a recent update - Mohd Padzil, Muhamad Faiz; Abdul Razak, Mariatulqabtiah; Abu, Jalila (Veterinary Association Malaysia, 2017)
Avian polyomavirus disease is among the most common viral diseases of domesticated exotic birds as such in psittacine families. Caused by avian polyomavirus (APV) which possess a circular, double-stranded DNA which encodes for major structural virus protein 1 (VP1) and minor structural proteins VP2, VP3 and VP4, the disease is also known as Budgerigar fledgling disease polyomavirus (BFPyV), Papovavirus, and Psittacine polyomavirus. Infections from APV may lead to cutaneous haemorrhage, abdominal distension, feather abnormalities and even death. The APV virus has a broad avian host range and is known to cause acute chronic disease in several psittacine birds such as parrot, cockatoo, macaw, and budgerigar. The current status of APV epidemiology globally has not been fully recorded. Only the studies of the virus and disease caused within several countries are used as references, and few were done together with detection of beak and feather disease virus. Despite the common occurrence of APV among bird breeders in Malaysia, a very limited study has been done to evaluate the prevalence status of APV in Malaysia. In this review, we wish to disseminate knowledge, particularly to pet owners and bird breeders, on APV characterisations, its updated occurrence worldwide and prevention strategies. This information may be useful to trigger in depth study on the epidemiology of disease and better management practises among breeders.